Root locus (Complex poles) - Jamadar, Afaqahmed (New Panvel AIKTC, School of Engg. & Tech., 2015)
Learning eResources created by AIKTC faculty. Method of solving complex type of problem.
Keywords: Mechanical Engineering; Electronic Resources